ANALISIS KESIAPSIAGAAN MASYARAKAT PADA WILAYAH RAWAN BANJIR LAHAR DINGIN GUNUNG GAMALAMA TERNATE (STUDI KASUS DI KELURAHAN DUFA-DUFA TERNATE) - Nasarudin, Nasarudin; Suwo, Rahedin; Kasnar, Suliamin (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2019)
This study analyzed the preparedness of the community of Dufa-Dufa Ternate in dealing with cold lava floods in the aspects of knowledge related to lava flood disasters, attitudes have been alert to disasters, and attitudes in dealing with disasters. Data collection techniques in this study used Likert scale questionnaire and in-depth interview technique. Data analysis technique in this research used descriptive analysis technique to saw the tendency of each variable. The results showed that people who had knowledge related to the lava flood disaster were 94.29% and those who did not had knowledge related to the lava flood disaster were 5.71%. In the aspect of public awareness attitude towards the lava flood disaster, the attitude of the people who always prepare plans before a disaster reaches 37.14%. In the category of frequent attitude of vigilance attained 50.00%. The attitude of the community in dealing with the cold lava flood disaster in an effort to improve their ability to attend disaster training was 37.14% strongly agreed, while the percentage of agreed was 50.00%. People who were hesitant about their ability to handle danger 8.57%. Increasing the capacity and knowledge of the community against disasters, the government needed to conduct training, outreach, and relocation for people who lived on the banks of the Tugurara river.